2005
DOI: 10.1159/000086337
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Pneumonitis due to Bunashimeji Mushrooms in the Mushroom Industry

Abstract: Background: Detection of hypersensitivity pneumonitis (HP) in employees involved in the Bunashimeji mushroom industry is difficult. The level of precipitating antibody is not related with the prediction of progression and resolution of HP. The aims of this study were to examine the actual prevalence of HP in the Bunashimeji industry and the clinical differences among selected employees. Methods: One hundred and fourteen employees worked in Bunashimeji enterprises. These subjects were divided into the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…These results suggest that mushroom factories can be considered as a significant risk factor for allergic diseases. Some previous studies have also demonstrated the important role of other types of basidiomycetous fungi in the induction of hypersensitivity-related reactions including HP in mushroom workers [15-17]. …”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that mushroom factories can be considered as a significant risk factor for allergic diseases. Some previous studies have also demonstrated the important role of other types of basidiomycetous fungi in the induction of hypersensitivity-related reactions including HP in mushroom workers [15-17]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have investigated the criteria by which HP patients should be diagnosed. Tsushima et al [2005] reported that serum KL-6 and SP-D may be related to the resolution of HP in addition to the LST values and chest CT. Kohno et al [1989] and Kobayashi and Kitamura [1995] reported that the serum KL-6 is a good marker for disease activity in interstitial pneumonitis such as HP. SP-A and SP-D are also known to be good markers indicating disease activity of HP Tanaka et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…A study was conducted among the remaining workers at the mushroom farms in the rural area to find new cases of HP caused by P. citrinum. Tsushima et al [2005] reported that serum Krebs von der Lungen-6 (KL-6) and surfactant protein (SP)-D may be related to the resolution of HP in addition to lymphocyte stimulation test (LST) values and chest CT. Some articles reported that the serum KL-6 is a good marker for disease activity in interstitial pneumonitis such as HP [Kohno et al, 1989;Kobayashi and Kitamura, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…C, D: No f i b r o t i c c h a n g e s we r e f o u n d [ C: e l a s t i c a v a n Gi e s o n , × 1 0 ; D: e l a st i c a v a n Gi e s o n , × 4 0 ] . (11). Positive responses to Penicillium citrinum were observed in PB and BAL fluid ( Table 2).…”
Section: Case Reportmentioning
confidence: 95%